1992
DOI: 10.1152/jappl.1992.72.1.383
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the accuracy of esophageal balloon measurement of pleural pressure in dogs

Abstract: Simultaneous measurement of esophageal and tracheal pressures during an occluded inspiratory effort was used to assess the accuracy of the esophageal balloon for measuring pleural pressure in dogs. Esophageal balloons were inserted in five mongrel dogs, and an occlusion test was performed with the balloon tip 5, 10, 15, 20, and 25 cm above the esophageal sphincter; at lung volumes of functional residual capacity (FRC) and FRC + 600 ml; and in supine and right- and left-side lying postures. The protocol was rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
1
18
0
2
Order By: Relevance
“…In most conditions, the majority of points centered along the line of identity, with correlation coefficients between 0.75 and 0.98 (Tables 1 and 2). 12 Despite these apparent problems, a combined esophageal balloon / nasogastric tube catheter appears to yield APes estimates similar to those obtained using a standard esophageal balloon of much smaller diameter.10·11 The graph for positive pressure ventilation shows generally positive values for APes, indicating that most subjects were not breathing passively, thereby introducing an unintended element of variability related to effort.…”
Section: Resultsmentioning
confidence: 94%
“…In most conditions, the majority of points centered along the line of identity, with correlation coefficients between 0.75 and 0.98 (Tables 1 and 2). 12 Despite these apparent problems, a combined esophageal balloon / nasogastric tube catheter appears to yield APes estimates similar to those obtained using a standard esophageal balloon of much smaller diameter.10·11 The graph for positive pressure ventilation shows generally positive values for APes, indicating that most subjects were not breathing passively, thereby introducing an unintended element of variability related to effort.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, it is important to ensure that the location of the balloon is standardised. The balloon was positioned in the caudal third of the oesophagus where pressure values have been shown to be most reliable and repeatable (Dechman et al . 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthily, other studies reported that an offset exists between absolute values of P pl and P es , and that the agreement between the changes in those two pressures is reduced in mechanically ventilated subjects, supine position, and injured (i.e. more heterogeneous) lungs [10][14].…”
Section: Introductionmentioning
confidence: 94%